Wapl releases Scc1-cohesin and regulates chromosome structure and segregation in mouse oocytes - Silva, Mariana C.C. (J Cell Biol, 2020)
Cohesin is essential for genome folding and inheritance. In somatic cells, these functions are both mediated by Scc1-cohesin, which in mitosis is released from chromosomes by Wapl and separase. In mammalian oocytes, cohesion is mediated by Rec8-cohesin. Scc1 is expressed but neither required nor sufficient for cohesion, and its function remains unknown. Likewise, it is unknown whether Wapl regulates one or both cohesin complexes and chromosome segregation in mature oocytes. Here, we show that Wapl is required for accurate meiosis I chromosome segregation, predominantly releases Scc1-cohesin from chromosomes, and promotes production of euploid eggs. Using single-nucleus Hi-C, we found that Scc1 is essential for chromosome organization in oocytes. Increasing Scc1 residence time on chromosomes by Wapl depletion leads to vermicelli formation and intra-loop structures but, unlike in somatic cells, does not increase loop size. We conclude that distinct cohesin complexes generate loops and cohesion in oocytes and propose that the same principle applies to all cell types and species.